Decision aids for prenatal testing: A systematic review and meta‐analysis. (3rd May 2021) - Yu, Lin; Yang, Shu; Zhang, Chunmiao; Guo, Pingping; Zhang, Xuehui; Xu, Mengmeng; Tian, Qi; Cui, Xuan; Zhang, Wei
Abstract: Aims: To analyse the effect of decision aids (DAs) used by pregnant women on prenatal testing decisions. Design: Systematic review and meta‐analysis. Data resources: We searched Embase, PubMed, Web of Science and the Cochrane Central Library ending October 2020. Review methods: Papers were selected for analysis in accordance with the PRISMA guidelines. The meta‐analysis was carried out using Review Manager 5.3 software. The quality of the studies was assessed using the risk of bias tool recommended by the Cochrane Handbook. The result is knowledge, decision conflict, anxiety and other secondary outcomes. Results: A total of 18 studies were included in the systematic review and meta‐analysis. Comprehensive analysis showed that DAs could significantly improve knowledge and decision‐making satisfaction, reduce decision conflict, increase the proportion of women who make informed choice and had no influence on anxiety and decision regret. Conclusions: This article systematically reviewed the positive effect of DAs on the decision‐making of pregnant women facing prenatal testing. In the future, nurses should be encouraged to develop DAs in accordance with strict standards and apply them to pregnant women of different backgrounds. Impact: There is a growing consensus that health care should be patient‐centred, and the values and preferences of pregnant women who undergo prenatal testing need to be incorporated into the clinical decision‐making process. This review reports that the use of DAs can increase pregnant women's chances of participating in prenatal testing decisions and may improve the quality of their decision‐making. It also provides information on the role and practice of nurses in promoting evidence‐based prenatal testing for DAs.